"Little Brown Brothers" height and the Philippine-American colonial encounter (1898-1946) - Lasco, Gideon (Quezon City Ateneo de Manila University, 2018)
"This article looks at how scientific racism, biomedicine, public health, sports, and a nascent bureaucracy intersected in the making of height (human stature) as an important attribute of individuals and populations during the Philippine-American colonial encounter. In relation to the "tall" Americans, Filipinos were depicted and problematized as "short," and the attention to children's growth, the rise of sports, and the establishment of a bureaucracy all contributed to making height a measure of health and a parameter of inclusion (and exclusion) in various domains of society."
Keywords: Bataan Nuclear Power Plant (BNPP); Public-Private Partnership (PPP); Anthropometry; Public health; Imperialism -- United States; Height